NUMERICAL ANALYSIS OF GLUED LAMINATED TIMBER WITH UNEQUAL LENGTHS COMPONENTS - ABBU, MUTHANNA; AL-AMERI, RIYADH (Journal of Duhok University, 2017)
An innovative study has been carried out on timber beams strengthened mechanically by two external layers attached to their tension and compression sides with glue. This study is based on the individual behavior of each component of the laminate section. An approach has been developed to simulate the behavior of such beams. The equations are formulated and solved numerically using finite difference method and computational analysis. The interaction efficiency indicated by slip and deflection calculations between the three layers in a timber beam has been considered thoroughly, from which the effect of some parameters such as layer length upon the behavior of such beams are studied. New equations are proposed for such system to calculate the deflection of laminated timber beams.